PO.2.27 Early changes in the circulating B cell compartment associated with response to treatment and occurrence of flares in patients receiving therapy for active systemic lupus erythematosus. (27th September 2022) - Gatto, M; Gomez Gonzales, A; Lindblom, J; Doria, A; Parodis, I
Abstract : Purpose: To investigate changes in B cell subsets and serological markers in relation to clinical response and flares in patients with systemic lupus erythematosus (SLE) treated with standard therapy (ST) with or without add-on belimumab. Methods: We analysed data from the BLISS-76, BLISS-SC and BLISS Northeast Asia trials (N=1712). Circulating CD19+ B cell subsets were determined by flow-cytometry. We studied associations of relative to baseline percentage changes in circulating B cell subsets, anti-dsDNA antibody and complement levels with SLE Responder Index (SRI)-4 response after 52 weeks of treatment or occurrence of disease flares during follow-up. B cell changes occurring through week 8 were termed 'rapid' and through week 24 'early'. Non-parametric tests were employed as appropriate. Results: In the entire cohort, more prominent decreases in CD20-CD27br plasmablasts (-44.9% vs. -33.3%; P=0.011), and CD20-CD138+ LLPC (-48.2% vs. -37.1%; P=0.024) were seen in SRI-4 responders (47.8%), while less prominent early decreases in CD20-CD138+ LLPC (-23.5% vs -39.4%; P=0.028) and CD27brCD38br SLE-associated plasma cells (-19.0% vs -27.8%; P=0.045) were shown in patients developing severe flares (12.2%), holding true for patients on ST alone. A rapid decrease in CD20+CD138+ short-lived plasma cells (-50.4% vs -16.7%; P=0.019) and CD20-CD27br plasmablasts (-50.0% vs -29.9%; P=0.020) followed by a subsequent return to near-baseline values distinguished patients developing a renal flare. By contrast, plasma cell subsets gradually decreased in patients who did not develop a renal flare. Memory B cells showed a more prominent rapid (+92.0% vs +66.7%; P=0.002) and early (+60.0% vs +49.5%; P=0.033) expansion in SRI-4 responders versus non-responders. After adjustment for rapid changes, early increases or no return after a rapid expansion in CD20+CD27+ memory B cells portended subsequent severe flares (HR: 1.58; 95% CI: 1.18–2.11). In stratified analysis, patients on ST developing renal flares exhibited a rapid decrease in the memory B cella (-34.8% vs 0.0%; P=0.006), while belimumab induced increases in memory B cells irrespective of renal flaring. SRI-4 responders on belimumab displayed rapid reductions in anti-dsDNA (-14.8% vs -8.7%; P=0.043) and increases in C3 (+4.9% vs +2.1%; P=0.014) and C4 levels (+11.5% vs +8.3%; P=0.017). Patients who developed flares of any severity showed no or less prominent rapid or early (P<0.001 for both) decreases in anti-dsDNA levels. Conversely, early changes in serological biomarkers did not distinguish patients developing renal flares. Conclusions: Specific changes in composition and pattern of circulating B cell subsets upon treatment for active SLE can portend disease flares or treatment response. Importantly, most B cell changes are related to treatment effectiveness rather than to treatment targets, although anti-B cell therapies can incite certain peculiar alterations which require awareness i.e. increasae in memory B cells. Modifications in circulating B cell subsets occur soon after treatment initiation and may therefore prove a useful complement in SLE patient surveillance and early treatment evaluation.